Predictive Optimal Matrix Converter Control for a Dynamic Voltage Restorer with Flywheel Energy Storage - Gambôa, Paulo; Silva, J. Fernando; Pinto, S. Ferreira; Margato, Elmano (IntechOpen, 2011)
None